Investigation on surface quality of high-speed cutting titanium alloy Ti6Al4V based on Split-Hopkinson pressure bar. (August 2020) - Zhang, Zhanfei; Wang, Zengqiang; Wang, Wenhu; Jiang, Ruisong; Xiong, Yifeng
High-speed cutting technology has the characteristics of high material removal rate and excellent processing quality. To investigate the surface quality of high-speed cutting Ti6Al4V alloy, the orthogonal cutting experiment is the cutting device based on improved Split-Hopkinson pressure bar carried out with a cutting speed of about 7–16 m/s. Surface roughness, residual stress and three-dimensional surface topography are examined to characterize the surface quality. And the chip geometry parameters are measured to analyze the formation mechanism of surface topography. The result shows that cutting force and surface roughness increase rapidly with the increase in depth of cut. In the meantime, the periodic microwaves appeared on the machined surface, and their amplitudes increase with the increase in depth of cut. However, surface roughness, residual stress and microwave amplitude all decrease with the increase in cutting speed. Moreover, it is found that the evolution trend of chip thickness and surface roughness with cutting parameters is very similar. Therefore, it can be inferred that there is a strong relationship between surface topography and chip morphology.